HUBUNGAN POLA PEMBERIAN MP-ASI DENGAN KEJADIAN STUNTING PADA BAYI USIA 6-24 BULAN - Evi Lusiana; Kinanti Pricilia Yunus; Rizky Pratiwi; Suriyani; Muaningsih (PT Nuansa Fajar Cemerlang, 2026)
Introduction: Stunting is still a chronic nutritional problem in children under five years of age which has an impact on physical growth, cognitive development and the quality of human resources in the future. One of the factors that plays an important role in preventing stunting is the practice of providing food in the early stages of life, especially the pattern of providing Complementary Feeding with Breast Milk (MP-ASI). The aim of this reasearch to determine the relationship between MP-ASI feeding patterns and the incidence of stunting in babies aged 6-24 months. Method: This research uses a quantitative, observational analytical design with a cross-sectional approach. The population in this study were mothers with children aged 6–24 months who visited the Kassi-Kassi Health Center. The research sample consisted of 63 respondents taken using total sampling techniques. Data was collected through a structured questionnaire to assess MP-ASI feeding patterns and anthropometric measurements to determine stunting status based on the body length index for age (PB/U) using the Z-score. Data analysis was carried out using the Chi Square test. Results: The research showed that 46 respondents (73%) had a poor pattern of giving MP-ASI, while 17 respondents (27%) had a good pattern of giving MP-ASI. The incidence of stunting was found in 49 children (77.8%), consisting of 31 children (49.2%) in the short category and 18 children (28.6%) in the very short category, while 14 children (22.2%) had normal nutritional status. The results of statistical tests show that there is a significant relationship between the pattern of giving MP-ASI and the incidence of stunting with a value of p = 0.000 (p < 0.05). Discussion: This study shows that there is a significant relationship between the pattern of giving MP-ASI and the incidence of stunting in children aged 6–24 months at the Kassi-Kassi Health Center. Therefore, increasing mothers' knowledge and practice in providing MP-ASI in accordance with nutritional recommendations is very necessary as an effort to prevent stunting and support optimal growth and development of children. Key words: MP-ASI, stunting, children aged 6–24 months